Influence of Hypoxic and Hyperoxic Preconditioning on Endothelial Function in a Model of Myocardial Ischemia-Reperfusion Injury with Cardiopulmonary Bypass (Experimental Study) - Irina A. Mandel (International Journal of Molecular Sciences, 2020)
The aim of the experiment was to evaluate the effect of preconditioning based on changes in inspiratory oxygen fraction on endothelial function in the model of ischemia-reperfusion injury of the myocardium in the condition of cardiopulmonary bypass. The prospective randomized study included 32 rabbits divided into four groups: hypoxic preconditioning, hyperoxic preconditioning, hypoxic-hyperoxic preconditioning, and control group. All animals were anesthetized and mechanically ventilated. We provided preconditioning, then started cardiopulmonary bypass, followed by induced acute myocardial infarction (ischemia 45 min, reperfusion 120 min). We investigated endothelin-1, nitric oxide metabolites, asymmetric dimethylarginine during cardiopulmonary bypass: before ischemia, after ischemia, and after reperfusion. We performed light microscopy of myocardium, kidney, lungs, and gut mucosa. The endothelin-1 level was much higher in the control group than in all preconditioning groups after ischemia. The endothelin-1 even further increased after reperfusion. The total concentration of nitric oxide metabolites was significantly higher after all types of preconditioning compared with the control group. The light microscopy of the myocardium and other organs revealed a diminished damage extent in the hypoxic-hyperoxic preconditioning group as compared to the control group. Hypoxic-hyperoxic preconditioning helps to maintain the balance of nitric oxide metabolites, reduces endothelin-1 hyperproduction, and enforces organ protection.